Review: Effect of Gut Microbiota and Its Metabolite SCFAs on Radiation-Induced Intestinal Injury - Li, Yangyang; Zhang, Yiming; Wei, Kongxi; He, Jinpeng; Ding, Nan; Hua, Junrui; Zhou, Ting; Niu, Fan; Zhou, Gucheng; Shi, Tongfan; Zhang, Liying; Liu, Yongqi (Frontiers in Cellular and Infection Microbiology, 2021)
Gut microbiota is regarded as the second human genome and forgotten organ, which is symbiotic with the human host and cannot live and exist alone. The gut microbiota performs multiple physiological functions and plays a pivotal role in host health and intestinal homeostasis. However, the gut microbiota can always be affected by various factors and among them, it is radiotherapy that results in gut microbiota dysbiosis and it is often embodied in a decrease in the abundance and diversity of gut microbiota, an increase in harmful bacteria and a decrease in beneficial bacteria, thereby affecting many disease states, especially intestine diseases. Furthermore, gut microbiota can produce a variety of metabolites, among which short-chain fatty acids (SCFAs) are one of the most abundant and important metabolites. More importantly, SCFAs can be identified as second messengers to promote signal transduction and affect the occurrence and development of diseases. Radiotherapy can lead to the alterations of SCFAs-producing bacteria and cause changes in SCFAs, which is associated with a variety of diseases such as radiation-induced intestinal injury. However, the specific mechanism of its occurrence is not yet clear. Therefore, this review intends to emphasize the alterations of gut microbiota after radiotherapy and highlight the alterations of SCFAs-producing bacteria and SCFAs to explore the mechanisms of radiation-induced intestinal injury from the perspective of gut microbiota and its metabolite SCFAs.